Anti bacterial activity of Cinnamomum zeylanicum and Capsicum annunm extracts against Escherichia coli and Salmonella typhi . - Maysoon M. Alhamando, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
Two Gram negative bacterial isolates were selected : Escherichia coli and Salmonella typhi . Antibacterial activity of the aqueous and alcoholic extracts of Cinnamomum zeylanicum and Capsicum annunm were determined against the two bacterial isolates . obtained results showed that the inhibitory concentration of the cinnamon aqueous extract was 150 mg/ml for E. coli and was 175 mg/ml for S.typhi . whereas The cinnamon ethanolic extract was 20 mg/ml for E. coli and was 10 mg/ml for S.typhi .The results indicated that , both extracts had a suppressing effects. The results proved also that the alcoholic extract for cinnamon has better effect than the aqueous extract against these two bacterial isolates . The results also showed that there is no effect for capsicum annum(black pepper) neither aqueous extracts nor alcoholic extract against the bacterial isolates that used in this study .